2013
DOI: 10.1016/j.biopsycho.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Neural time course of threat-related attentional bias and interference in panic and obsessive–compulsive disorders

Abstract: Attentional biases to threat are considered central to anxiety disorders, however physiological evidence of their nature and time course is lacking. Event-related potentials (ERPs) characterized sensory and cognitive changes while 20 outpatients with panic disorder (PD), 20 with obsessive-compulsive disorder (OCD), and 20 healthy controls (HCs) responded to the color (emotional Stroop task) or meaning of threatening and neutral stimuli. ERPs indicated larger P1 amplitude and longer N1 latency in OCD, and short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 139 publications
(178 reference statements)
0
27
1
8
Order By: Relevance
“…Several studies now have found higher P1 amplitude to threat stimuli in clinical anxiety, and some have found faster latencies. For example, Thomas et al (2013) found larger P1 amplitude in the obsessive-compulsive disorder group, and shorter P1 latency in the panic disorder group to threat stimuli versus neutral stimuli. Participants with emotional Stroop interference had augmented P1 amplitude to threat (versus neutral) stimuli when color-naming.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies now have found higher P1 amplitude to threat stimuli in clinical anxiety, and some have found faster latencies. For example, Thomas et al (2013) found larger P1 amplitude in the obsessive-compulsive disorder group, and shorter P1 latency in the panic disorder group to threat stimuli versus neutral stimuli. Participants with emotional Stroop interference had augmented P1 amplitude to threat (versus neutral) stimuli when color-naming.…”
Section: Discussionmentioning
confidence: 93%
“…P1, N1, and P2 components may indicate relatively early sensory stages of information processing. For example, the P1 is presumed to be associated with early visual processing (Thomas et al, 2013), N1 is thought to reflect attentional focus on targets and a discrimination process within the focus of attention (Frings and Groh-Bordin, 2007), and P2 has been associated with low-level word processing (Coles and Rugg, 1995;Crowley and Colrain, 2004). N2 and P3 components reflect the capture of attention during later, higher-level cognition including inhibitory and memoryupdating processes; and P3 in particular appears to be associated with stimulus evaluation (Dai and Feng, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…In particular, these studies have confirmed that the emotional Stroop task activates the rostral subdivision of the anterior cingulate cortex [15]. Dresler et al [16] used the emotional Stroop task in conjunction with fMRI to investigate the attentional bias toward threat-related words in PD patients.…”
Section: Introductionmentioning
confidence: 86%
“…The exhibited Stroop interference for threat-related words can be perceived as the result of an attentional bias; exhibited Stroop interference in relation to social threat or specific panic words, however, has been subject to controversy [9]. On the contrary, some researchers think that the emotional Stroop task (as well as other cognitive tasks) measures only indirect evidence (e.g., reaction time impairment in the presence of threat stimuli) of attentional bias [13, 15, 16]. They have argued that studies suggesting impaired Stroop task performance in PD only quantified attentional biases associated with measurable behavioral changes (i.e., anxiety-related symptoms), but these biases might occur even in healthy controls, independently of behavioral interferences.…”
Section: Introductionmentioning
confidence: 99%